Study of Farmers Response to Sugar Cane Agroindustry Development Plan in West Muna Regency - Muhammad, Yekim; Rianda, La; Sakir, Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
Â This study aims to determine the response of farmers to the sugarcane agroindustry development plan and to determine the factors that influence the response of farmers to the sugarcane agroindustry development plan in West Muna Regency. The method of data analysis uses proportion test and multiple linear regression analysis. The results showed that (1) the level of community response to the sugarcane agroindustry development plan was in the medium category. (2) Age and expected benefits have a significant positive effect on agro-industry development plans. Factors that did not significantly affect the community's response to the sugar cane agroindustry development plan were the level of education, farming experience, land area, and the number of family dependents.